PENDIDIKAN MORAL DALAM PERSPEKTIF SHAYKH NAWAWI AL-BANTANY - Dian Mohammd Hakim (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2019)
The perfectness of human being will be transmitted through Akhlaq (ethics). These ethics covered the standart of good habit and bad habit. Both of them are defined in the moral education concept. Shaykh Nawawi Al-Bantany with hisMaraqi al-’Ubudiyah, Syarh ’alaMatn Bidayah al-Hidayah explained that ethics.Therefore, it is needed deep study about it. Particularly, the contemplations and materials which will form good moral and avoid moral from the destruction, the moral role in shaping a good man, and the relevance of moral education. Content analysis technique will be used in the study. Content analysis is emphasized in how the researchers view a content of communications qualitatively. The result showed that; the concept of moral education is about moral advises. The material sare divided into moral education for the individual and its relationship with his God, family, and another people, and the role of moral education assign post so reminders of the individuals thems elves, and the relevance concept of moral education of Islamic educationis lessen couraging to the power of creativity, work ethic andethos ofscience. Keyword: Islamic Education, Aswaja NU, Radicalism